The Concept of Solid Waste Management from an Islamic-Based Development Worldview Perspective - Abang Mohd. Razif Abang Muis; Abdul Hair Beddu Asis; Fadzila Azni Ahmad (Pennwell Corporation, 2020)
Conventional solid waste management treats the operational and technical aspects as the main aspects in its implementation. There are at least four main issues in solid waste management, which are society’s attitude that does not lend priority to environmental cleanliness, inefficient human development management, inefficient waste storage and transportation facilities and conflict in the solid waste disposal process. These are some of the main challenges that should be overcome in order to ensure that a resourceful and sustainable management of solid waste is achieved. Hence, this study has two objectives, which is to identify the solid waste management concept and analyse the concept from an Islamic-based development worldview perspective. Data were obtained using the document study method and analysed using the content analysis method. Findings show that the solid waste management concept from an Islamic-based development worldview perspective comprises four main components, namely monotheism (tauhid), actors, values and the main objective. It can be concluded that the four main components should be assimilated and emphasised to form a better, resourceful and sustainable solid waste management concept.